Early Modern Humans and Morphological Variation in Southeast Asia: Fossil Evidence from Tam Pa Ling, Laos - Demeter, Fabrice; Shackelford, Laura; Westaway, Kira; Duringer, Philippe; Bacon, Anne-Marie; Ponche, Jean-Luc; Wu, Xiujie; Sayavongkhamdy, Thongsa; Zhao, Jian-Xin; Barnes, Lani; Boyon, Marc; Sichanthongtip, Phonephanh; et al. (PLOS ONE, 2015)
Little is known about the timing of modern human emergence and occupation in Eastern Eurasia. However a rapid migration out of Africa into Southeast Asia by at least 60 ka is supported by archaeological, paleogenetic and paleoanthropological data. Recent discoveries in Laos, a modern human cranium (TPL1) from Tam Pa Ling‘s cave, provided the first evidence for the presence of early modern humans in mainland Southeast Asia by 63-46 ka. In the current study, a complete human mandible representing a second individual, TPL 2, is described using discrete traits and geometric morphometrics with an emphasis on determining its population affinity. The TPL2 mandible has a chin and other discrete traits consistent with early modern humans, but it retains a robust lateral corpus and internal corporal morphology typical of archaic humans across the Old World. The mosaic morphology of TPL2 and the fully modern human morphology of TPL1 suggest that a large range of morphological variation was present in early modern human populations residing in the eastern Eurasia by MIS 3.